Pogrzeby i formy pośmiertnego uhonorowania członków rodziny cesarskiej w okresie pryncypatu Augusta i Tyberiusza - Sawiński, Paweł (Studia Europaea Gnesnensia, 2012)
During the principate of Augustus and Tiberius, the unexpected death of members of the ruling house, the planned successors in particular, repeatedly disrupted the dynastic concepts of these emperors. The situation provided a good opportunity for the senate and the inhabitants of the provinces to assert their loyalty and attachment to the imperial family through appropriate honours paid to its departed members. Among numerous posthumous honours granted to the deceased, particular attention is due to the honorific arches and statue groups which were erected in major locations in Romeand in the provinces. The regulations of the Senate and the local authorities also concerned apposite commemoration of the anniversary of their death. As the epigraphic sources inform, on that day Roman citizens were subject to a number of prohibitions, while in front of the Mausoleum of Augustus ceremonial offerings (inferiae) were to be made to their Manes. The kinds of posthumous honours voted in honour of the deceased members of the domus Augusta attest to a high rank of these persons. After all, a similar kind of posthumous honours were bestowed only on the princeps. The analysis of the course and the nature of funeral ceremony of the members of Augustus’ and Tiberius’ house demonstrates that a certain model emerged, which since the funus of Marcellus was later imitated, with certain modifications, during funerals of successive representatives of the ruling dynasty. Among the shared elements which featured at those ceremonies one should list the public presentation of the body of the deceased at the Forum Romanum, funeral speeches (laudationes) delivered by the closest male members of the family and the display of the masks of the ancestors (imagines). There is no doubt that the funeral ceremonies of persons from the imperial family were a source of substantial inspiration in the arrangements for the funeral of Augustus himself, and later for the subsequent principes of the Julio-Claudian dynasty as well.